ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AGRESIVITAS PAJAK - Fung Njit Tjhai; Haikal (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to obtain empirical evidence about the factors influence of manajerial ownership, independent commissioner, corporate social responsibility, leverage, likuiditas, profitability, and inventory capacity. This research used sample of non-financial companies listed on the Indonesia Stock Exchange from 2018 to 2020. The method used in sample selection using purposive sampling methode, that the sample obtained is 142 companies. Hypothesis testing in the research uses multiple regression method. The results of this research concluded that profitability variable has positive influence on tax aggressiveness but manajerial ownership, independent commissioner, corporate social responsibility, leverage, likuiditas, and inventory capacity variable has no influence on tax aggressiveness